1995
DOI: 10.1111/j.1365-3024.1995.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Avian coccidiosis: changes in intestinal lymphocyte populations associated with the development of immunity to Eimeria maxima

Abstract: The effect of infection and subsequent challenge with Eimeria maxima on the populations of lymphocytes in the small intestine of Light Sussex chickens was assessed by immunohistochemistry. T cells were characterized for CD3, CD4, CD8, TCR1 (gamma delta heterodimer) or TCR2 (alpha beta 1 heterodimer) markers, and B cells for the expression of IgM, IgA and IgG. After a primary inoculum there were, in both the epithelium and the lamina propria, two distinct increases in the numbers of T lymphocytes. The first pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 33 publications
4
24
4
Order By: Relevance
“…Gut infiltration by γδTCR + T cells was also observed in primary avian and murine Eimeria infections (Findly et al 1993;Rothwell et al 1995). Considering that these cells contribute to 40% or more of PBMC in young calves (Wilson et al 1996) this cell type may be of particular importance in cattle.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Gut infiltration by γδTCR + T cells was also observed in primary avian and murine Eimeria infections (Findly et al 1993;Rothwell et al 1995). Considering that these cells contribute to 40% or more of PBMC in young calves (Wilson et al 1996) this cell type may be of particular importance in cattle.…”
Section: Discussionmentioning
confidence: 87%
“…According to these (Rothwell et al 1995;Shi et al 2001;Vervelde et al 1996), immunohistological analyses of parasitized gut mucosa revealed infiltration of CD4 + T cells early after infection (8 days p. i.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chickens, the gutassociated lymphoid tissue (GALT) is responsible for inducing immune responses against bacterial, viral, and parasitic enteral antigens as well as responses to innocuous antigens [11][12][13][14][15]. In the cecal tonsil (CT), the largest lymphoid organ of the avian GALT, which both T and B cells, are present in germinal centers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Extrathymic CD4 þ CD8 þ T cells in pigs increase with age and are considered to be mature antigen-experienced memory/ effector cells (Pescovitz et al, 1994;Zuckermann & Husmann, 1996). The levels of ªä T cells increase in response to a variety of infections in different species such as mice (Hiromatsu et al, 1992), young cattle (Koets et al, 2002), chickens (Rothwell et al, 1995) and humans (Munk et al, 1990). These cells are considered important in the early response against infections at epithelial surfaces (Skeen & Ziegler, 1993;Boismenu & Havran, 1994;Ishigami et al, 1999) and in the immune response of young pigs before maturation of other lymphocyte subsets (Yang & Parkhouse, 1996).…”
Section: Numbers Of Circulating Cd4mentioning
confidence: 99%